DAMPAK KEPEMIMPINAN TRANSFORMASIONAL DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI WISATA PANTAI LON MALANG SAMPANG - Radiva Dianda Zahra Putri; Samsuki Samsuki (Journal of Economic, Bussines and Accounting (COSTING), 2024)
Employees in the beach tourism industry in Lon Malang, Sampang Regency will be the focus of this study, which aims to examine the influence of transformational leadership and work environment on their employee productivity. This study looks at how transformative leader style and work environment affect productivity in the tourism industry. Information was collected from a survey given to all staff members of Lon Malang beach tourism. Saturated sampling was the technique used to collect data in this study; 38 participants were all Lon beach tourism workers. Both primary hypothesis testing and classical hypothesis testing were used in the data analysis of this study. To fully understand the interaction between the variables under investigation, the data was subjected to multiple linear regression analysis. The anticipated findings of this study will show that transformational leadership style and work environment have a significant and positive impact on employee performance at Lon Beach Malang